Twenty-First Annual IEEE Applied Power Electronics Conference and Exposition, 2006. APEC '06.
DOI: 10.1109/apec.2006.1620601
|View full text |Cite
|
Sign up to set email alerts
|

Fast Lead-Acid Battery Charge Strategy

Abstract: This paper discusses the fast charge strategy due to the fact that one of the limitations of the lead-acid batteries is the long charging time. The fast charge strategy uses two phases in order to reduce the charging time and obtain high performance without reduced the lifetime battery. In the first phase is used constant high current and in the second phase is used current pulses controlled by a PID controller.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 4 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…In order to verify the correct operation of the optical fiber in real measurements in batteries, tests were carried out during the processes of charging and discharging using a testing bench which includes an automated system for the charge and discharge of batteries with different charging regimes [ 28 , 29 ]. Figure 13 shows the real time results for a slow charge (15 A), medium charge (51 A) and fast charge (150 A).…”
Section: Optical Fiber Point Sensormentioning
confidence: 99%
“…In order to verify the correct operation of the optical fiber in real measurements in batteries, tests were carried out during the processes of charging and discharging using a testing bench which includes an automated system for the charge and discharge of batteries with different charging regimes [ 28 , 29 ]. Figure 13 shows the real time results for a slow charge (15 A), medium charge (51 A) and fast charge (150 A).…”
Section: Optical Fiber Point Sensormentioning
confidence: 99%
“…Moreover, bipolar pulses produced by inverters can be used in the reflex charging mode [24]. Compared with the traditional DC power charging process, the reflex charging mode can speed the charging process up and extend the life of batteries [21,[25][26][27]. Generally, inverters are classified into voltage source inverters (VSIs) and current source inverters (CSIs) by considering the structure of the inverters [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…J. 2022, 13, x FOR PEER REVIEW 2 of 24 process up and extend the life of batteries [21,[25][26][27]. Generally, inverters are classified into voltage source inverters (VSIs) and current source inverters (CSIs) by considering the structure of the inverters [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…This increased charging efficiency to a great extent when compared to the old charge modes. In 2006, Marcos proposed a fast charge control [6] method, and the final experimental data showed that the battery temperature rise was improved effectively, which had an indirect effect on charging efficiency. In 2012, Hsieh and Shih compared the charging efficiency in different MPPTs [7].…”
Section: Introductionmentioning
confidence: 99%